THE OFFICE BUILDING AT JUŽNI BULEVAR 10, BELGRADE - Ivanović Vojvodić, Jelena; Vojvodić, Goran (Arhitektura i urbanizam, 2021)
In the process of total reconstruction and extension of the existing building in Južni bulevar, architects from the Biro VIA, led by Goran Vojvodić and Jelena Ivanović Vojvodić, designed the office building according to requirements of modern business. The building is characterized by a simple form with glass curtain wall, an accentuated rhythm of opening, and an emphasized colonnade of the access zone, which establishes a dialogue with the environment and users. Functional and decorative lighting composes different ambiences in the interior, and the change of shades and intense colors gives emphasis to the colorful anemia of facade and interior finishes. Among numerous awards and recognitions, the authors of this work won the prestigious award in the category of Architecture at the 41st Salon of Architecture.